Scientific, Cultural and Religious Services of Bani Bagtakin or Arbil Atabaks (before 592-630AH 1145-1223AD). - Hasheminia, Seyyed Mohammadreza; Torbatinezhad, Behjat (Journal of Islamic History, 2024)
Abstract Seljuks had a major role in political, racial, religious, economic, social, and cultural developments in Islamic lands under their territory. The Atabaki entity was introduced to Islam by Seljuk Turks. This study is to examine the scientific, cultural, and religious services of the Arbil Atabaks (Bani Bagtakin) government, which made their government last for about a century. According to the political, cultural, social, and military conditions and also the conflicts of local government in this period, many scholars and jurists were raised in the territory of Arbil Atabaks, and many books were written in a variety of fields. At this time many mosques, schools, orphanages, workhouses, hospitals, and monasteries were established, too. Mozaffar ad-Din Kokabori who was a famous ruler of this family took action for the welfare of the people, his actions included the improvement of roads, the establishment of security, the building of castles, and the repair of Bi’rmeimoun in (604 AH), which were very significant historically. In this period, the birthday of the Prophet Muhammad (PBUH) was celebrated for the first time in history. The Research Methodology of this study is Descriptive- Analytical and the data collection method is library-based. An attempt was made to examine the issue by means of relevant and main sources. Keywords: Cultural-Religious, Atabaks Territory, Seljuk Turks, Muzaffaruddin Kokabori, Bi’rmeimoun REFERENCE Ebrahim Hassan, Hassan, 1386. Political history of Islam. translated by Abul Qasem Payandeh, Alami Farhani, Tehran. Bosworth, Clifford Edmond, 1381, Islamic dynasties and a guide to Islamic chronology and genealogy, translated by Fereydoun Badraei, Islamic and Iran Research Center, Tehran. Abu Shameh, Abd al-Rahman, 1997, Al-Dhail Ali Al-Ruzateen (Translations of Men) by Ebrahim, Zaibaq, Beirut. Ibn Athir, Ezzuddin Abul Hasan Ali, 1415 AH 1995 AD, Al-Kamal by the efforts of Abul Fida Abd Allah Qazi, Beirut. Sabbat Ibn Jozi, Yusuf, 1371 AH, 1952 AD, Marah Al-Zaman, Hyderabad Deccan. Ibn Khalqan, Ahmad bin Muhammad, 1381, death of Al-Aiyan, Shuja Sanjari, translated by Fatemeh Madrasi, Tehran. Ibn Wasil, Muhammad bin Salem, 1395 AH 1975 AD, Mufaraj al-Karoob by Hasnain, Muhammad, Rabi, Cairo. Dhahabi, Muhammad bin Ahmad, 1948 AD, Al-Abar, with the efforts of Salahuddin Monjad, Kuwait. Ibn Ibri, 1986, Tarikh al-Zaman, translated by Ishaq, Ermela, Beirut. Naimi, Abd al-Qadri, 1410 A.H., al-Daras fi al-tarikh al-madaris, by Ebrahim Shams al-Din, Beirut Ibn Khalqan, 1964, Deaths, Ibn Shaddad, Yusef, Al-Nawad al-Sultaniyyah, with the efforts of Jamal al-Din Shiyal, Cairo. Ashraf al-Rasuli, Ismail, 1395 AH 1975 AD, Al-Asjad al-Masbuk, by the efforts of Shakir Mahmoud Abdul-Moneim, Baghdad, Beirut. Dhahabi, 1413 AH, Sira Alam al-Nabla, by the efforts of Shoaib Arnaut and Mohammad Naeem Argasousi, Beirut Sajjadi, Sadegh, 1383, Bani Bagtkin, "Big Islamic Encyclopaedia", Tehran. Musaheb, Gholam Mohsin, 1374, "Persian Encyclopaedia", Amir Kabir, Tehran. Osama bin Pohr, 1930, credit to Philip Hatt, Princeton. Ibn Ibri, Grigorios, 1890 AD, Tarikh al-Dul, Beirut. Ibn Adim, Umar, 1988, Baqiyyah al-Talab, by Sohail Zakar, Beirut Rashid Nazem, 1973 AD, "Al-Shaarfi Erbil fi Zal al-Asra al-Baktkiniyah between (526-630 AH)", September, Adab al-Rafidin, al-add 9 Qazvini, Zakaria bin Muhammad, 1373, Works of Al-Balad and Akhbar al-Abad, translated by Mirza Jahangir Qajar, Amir Kabir, Tehran. Zidan, George, 1386, History of Islamic Civilization, translated by Ali Javaherkalam, Amir Kabir, Tehran. Tabari, Muhammad bin Jarir, 1413 AH, 1992 AD, Tarikh Tabari, Abdul Ghani Aref, Damascus. Fasi, Muhammad bin Ahmad, 1386 AH, Shifa, Al-Gharam Baakhbar al-Balad al-Haram, Muhammad Moghaddis, Mashaar Publishing House, Dar al-Kitab Al-Alamiya, Beirut Aruzqi, Muhammad bin Abdullah, 1275 AH 1858 AD, Akhbar Al Makkah, by the efforts of Westenfeld, Gottinken, translated by Mahmoud Mahdavi Damghani, Hekmat, Tehran Hamdani, Hassan, 1383 AH 1963 AD, Al-Aklil, by the efforts of Muhammad bin Ali Akua, near Cairo. Dinouri, Ahmed, 1960, Al-Akhbar al-Tawal, Abd al-Moneim Amer Jamal al-Din Shiyal, Cairo. Ibn Fahd, Umar, 1403 AH 1983 AD, Ithaf al-Wori, by the efforts of Fahim Muhammad Shaltut, Mecca. Tawfiq al-Aboud, Madras al-Iraqiyya outside Baghdad in al-Asr al-Abbasi, College of Literature, Society of Baghdad. Ibn Athir, 1415 AH 1963 AD, Al-Tarikh al-Bahir, by the efforts of Abdul Qadir Ahmad, Talimat Cairo Baghdad.. Yaqut, Shahab al-Din Abu Abdullah al-Hamowi, 1381, Majam al-Adba, translated by: Abd alHamid Aiti, Soroush, Tehran. Anoushe, Hassan, 1369, Culture of Biographies, Raja Cultural Publishing House, Tehran. Asnawi, Abd al-Rahim bin Hasan, Tabqat al-Shafaiyya, Dar al-Kitab Dhahabi, 1988, Tarikh al-Islam and the deaths of famous people, Al-Rasalah Institute, Beirut. Modares Tabrizi, Mohammad Ali, 1374, Rehaneh Al-Adab, in the description of the lives and works of scholars, mystics, jurists, philosophers, poets, great Islamic calligraphers from the beginning to the present era..., Khayyam, Tehran, 4th edition